Analisis Faktor-Faktor yang Mempengaruhi Hasil Belajar Siswa Kelas V pada Mata Pelajaran Matematika di Sekolah Dasar Islam Al-Muhajirin Cilegon (Jurnal Manajemen Kreatif dan Inovasi, 2025)
The learning process is the implementation of the curriculum in educational institutions to influence students to achieve predetermined goals. Lack of student enthusiasm in the learning process results in learning outcomes that are not optimal. The purpose of the study was to analyze the influencing factors and teacher strategies in improving the learning outcomes of fifth grade students in Mathematics at Al-Muhajirin Islamic Elementary School. The method used is qualitative. Data collection techniques with observation, interviews and documentation. The research findings show that student learning outcomes at Al-Muhajirin Islamic Elementary School are classified as good, but there are still students with low learning outcomes. This can be seen from the average score of the midterm exam which although it is quite satisfying, but there are students who have not reached the standard of completeness. The research conclusions include the supporting and inhibiting factors for student learning outcomes. Internal supporting factors include motivation and attitude, while external supporting factors come from relationships with parents, teachers and the environment. Meanwhile, internal inhibiting factors are motivation, intelligence, interest and talent, self-confidence, and discipline. External inhibiting factors include family, school and peer environment. The teacher's strategy in improving student learning outcomes is to provide motivation, use varied learning strategies, provide learning methods that are in accordance with the situation and conditions of students and use interesting learning media in accordance with learning materials.